The Principle of Freedom of Contract in Agricultural Product Sharing based on Islamic Law - Bakung, Dolot Alhasni; Abdussamad, Zamroni; Muhtar, Mohamad Hidayat (Universitas Negeri Gorontalo, 2022)
Islamic financial scheme in practice is still causing problems in the wider community due to differences in perceptions that exist in the community. The principle of freedom of contract in Law No. 2 of 1960 concerning agricultural product sharing and Islamic law, especially related to agricultural product sharing and Article 1338 paragraph (1) of the civil code which stipulates that a legally made Agreement will apply like a law for the maker (Pacta Sunt Servanda principle), the word â€œallâ€ means that every legal subject can make an agreement whose contents are about anything, legal subjects have the freedom to determine the form of the agreement. This normative research aims to analyse the legal ramifications of violating the concept of freedom of contract in agricultural product sharing from the viewpoints of Islamic law. This result of this article found that the implementing of the revenue sharing system did not get a fair share, this was because at the time of the contract, farmers were in a weak position due to the need for money for children's education and other emergency needs, especially during the Covid-19 pandemic. The owner of the land has the right to obtain part of the crop on the farm managed by the cultivator and receive back the return of the land upon completion of the agreement.